Molecular Detection of Borrelia Bacteria in Cerebrospinal Fluid-Optimisation of Pre-Analytical Sample Handling for Increased Analytical Sensitivity - Malin Lager; Peter Wilhelmsson; Andreas Matussek; Per-Eric Lindgren; Anna J. Henningsson (Diagnostics, 2021)
The main tools for clinical diagnostics of Lyme neuroborreliosis (LNB) are based on serology, i.e., detection of antibodies in cerebrospinal fluid (CSF). In some cases, PCR may be used as a supplement, e.g., on CSF from patients with early LNB. Standardisation of the molecular methods and systematic evaluation of the pre-analytical handling is lacking. To increase the analytical sensitivity for detection of Borrelia bacteria in CSF by PCR targeting the 16S rRNA gene, parameters were systematically evaluated on CSF samples spiked with a known amount of cultured Borrelia bacteria. The results showed that the parameters such as centrifugation time and speed, the use of complementary DNA as a template (in combination with primers and a probe aiming at target gene 16S rRNA), and the absence of inhibitors (e.g., erythrocytes) had the highest impact on the analytical sensitivity. Based on these results, a protocol for optimised handling of CSF samples before molecular analysis was proposed. However, no clinical evaluation of the proposed protocol has been done so far, and further investigations of the diagnostic sensitivity need to be performed on well-characterised clinical samples from patients with LNB.